2018
DOI: 10.1172/jci121842
|View full text |Cite
|
Sign up to set email alerts
|

STING-mediated inflammation in Kupffer cells contributes to progression of nonalcoholic steatohepatitis

Abstract: Deficiency of STING attenuated MCD-induced hepatic steatosis and fibrosis in mice. WT and STING-deficient mice (Tmem173 gt) were fed with MCD for 8 weeks to induce NASH. H&E (Figure 1A) and Masson staining (Figure 1B) revealed steatosis, ballooning, inflammation, and fibrosis in the livers of MCD-fed mice, which was attenuated by deficiency of STING. Levels of cholesterol (Figure 1C), triglyceride (Figure 1D), and hydroxyproline (a marker of fibrosis, Figure 1E) in livers and levels of ALT (Figure 1F) and aspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
230
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(261 citation statements)
references
References 39 publications
9
230
1
Order By: Relevance
“…For example, Tmem173 (also known as stimulator of interferon genes [STING]) expression was significantly increased in livers of mice with NASH as compared with mice with isolated steatosis in our study (Figure D), promoting us to hypothesize that targeting STING might be a good way to prevent NASH progression. Consistently, three studies published very recently provided various evidence to prove that activation of STING pathway contributes to liver inflammation and the progression of NASH . In addition, we observed that the mRNA of stearoyl‐CoA desaturases 1 ( Scd1 ) was significantly higher in mice with NASH (Figure D), which was consistent with the previous study that overexpression of SCD aggregated while pharmacological inhibitors of SCD attenuated liver fibrosis .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For example, Tmem173 (also known as stimulator of interferon genes [STING]) expression was significantly increased in livers of mice with NASH as compared with mice with isolated steatosis in our study (Figure D), promoting us to hypothesize that targeting STING might be a good way to prevent NASH progression. Consistently, three studies published very recently provided various evidence to prove that activation of STING pathway contributes to liver inflammation and the progression of NASH . In addition, we observed that the mRNA of stearoyl‐CoA desaturases 1 ( Scd1 ) was significantly higher in mice with NASH (Figure D), which was consistent with the previous study that overexpression of SCD aggregated while pharmacological inhibitors of SCD attenuated liver fibrosis .…”
Section: Discussionsupporting
confidence: 92%
“…Consistently, three studies published very recently provided various evidence to prove that activation of STING pathway contributes to liver inflammation and the progression of NASH. [32][33][34] In addition, we observed that the mRNA of stearoyl-CoA desaturases 1 (Scd1) was significantly higher in mice with NASH ( Figure 3D), which was consistent with the previous study that overexpression of SCD aggregated while pharmacological inhibitors of SCD attenuated liver fibrosis. 35 We have several more potential targets selected from the transcriptome results are being investigated currently.…”
Section: Bril F Et Al Revealed That Tg Accumulation In Livers Of Patisupporting
confidence: 91%
“…KCs express the highest levels of inflammasome components among liver cell types, and NLRP3 activation in KCs promotes IL‐1β secretion fueling the progression of NASH . Activation of the NLRP3 inflammasome in KCs can be caused by mitochondria DNA release in response to NEFA or through the stimulator of interferon (IFN) genes, which induces inflammation through nuclear factor kappa B …”
Section: Mechanisms Of Inflammationmentioning
confidence: 99%
“…All above bring out hepatic inflammation and hepatocytes apoptosis (186). In this model, mice with deficiency of STING presents alleviated insulin resistance and lower levels of low-density lipoprotein in serum, and also decreased hepatic inflammation and fibrosis/steatosis, in which hepatic macrophages/kupffer cells may take a big part (187,188). Lipotoxicity can induce p62 to be phosphorylated through the cGAS-STING-TBK1 pathway, which causes aggravated protein inclusions in hepatocytes and it indicates that p62 could be a biomarker for NASH prognosis (189).…”
Section: Cgas-sting Pathway In Autoimmune or Inflammatory Diseasesmentioning
confidence: 99%